Opto-electronic characterization of TiO₂/Metal/TiO₂ multilayers - Valluzzi, Marcos G. (2017)
Transparent conductive oxides (TCOs) play an important role in many optoelectronic devices such as solar cells, organic light emitting diodes, touch panel and efficiency energy applications, heat mirrors and thermoelectric materials. In recent years, many researchers proposed a TCO/metal/TCO multilayer structure with advanced electrical properties, mechanical flexibility, chemical stability and high optical transparency than a TCO single layer. Multilayer films of TiO₂/Cu/TiO₂ and TiO2/Co/TiO2were grown on glass substrate by DC magnetron sputtering technique at low temperature deposition for low cost applications. Copper interlayer was chosen as a possible replacement of Ag due to their comparable electrical conductivity and relativity low cost. Cobalt interlayer is studied for ferromagnetic properties at room temperature because of its potential applications in spintronics. The deposition time was chosen to obtain estimated thickness for layers of 30 nm while metal interlayers of 12, 15 and 18 nm thick were grown. The optical, electrical, structural and morphological properties of these films were characterized by UV-visible spectroscopy, four probe technique, X-rays diffraction patterns and atomic force microscopy (AFM) respectively. Figures of merit (FOM) are determinate for transparent solar cells electrode and others applications.